1994
DOI: 10.1111/j.1600-0528.1994.tb01570.x
|View full text |Cite
|
Sign up to set email alerts
|

Age and order of eruption of primary teeth in Spanish children

Abstract: A longitudinal study on primary tooth eruption was performed in 114 Spanish children in two Primary Care Centers over 3 yr. Data from periodic observations and data collected by previously instructed parents was studied. Ages of tooth eruption were calculated for both sexes. Comparison between the two sides of the jaws showed a nonsignificant tendency towards earlier left side eruption. Comparison between maxillary and mandibular showed a significant earlier mandibular eruption for central incisors and second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
15

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 16 publications
0
10
1
15
Order By: Relevance
“…Furthermore, dental formulas are used to estimate biological age and to track children's growth (10). Longitudinal studies provide information on the ages of eruption of individual teeth, along with their variations (4,5,11,12) unclear in the literature (11). Oziegbe et al (16) suggested genetic and molecular studies to confirm the possible association of earlier emergence times of primary teeth to accelerated growth in boys during the first trimester.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, dental formulas are used to estimate biological age and to track children's growth (10). Longitudinal studies provide information on the ages of eruption of individual teeth, along with their variations (4,5,11,12) unclear in the literature (11). Oziegbe et al (16) suggested genetic and molecular studies to confirm the possible association of earlier emergence times of primary teeth to accelerated growth in boys during the first trimester.…”
Section: Discussionmentioning
confidence: 99%
“…Paediatricians' opinion regarding the timing of eruption of primary teeth is often sought by the parents. Primary teeth have shown wide variations in their eruption pattern and time as well between different population, ethnic and racial groups (2)(3)(4)(5). Other suggested factors which affect the eruption time may include gestational period (6), diseases (7), nutritional status and growth (8).…”
Section: Introductionmentioning
confidence: 99%
“…Using the illustrative data set in the current investigation, T was set to the end of each age range associated with each examination of the cohort study, approximately 8.4 years, 9.8 years and 11.8 years, plus an estimate of the age on eruption of primary molar teeth obtained from Ramirez et al [1994].…”
Section: Statistical Modelmentioning
confidence: 99%
“…Most parents consider tooth eruption an important event in the child's development; hence, they often are anxious about timing and the sequence of eruption. Several studies have shown variations in the ages at which individual primary teeth erupt [1][2][3] as well as variations of eruption patterns between different ethnic and racial groups. [4][5][6] It is desirable to have suitable reference standards which ensure international comparability to assist clinicians in diagnosing cases of delayed or advanced tooth eruption.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] It is desirable to have suitable reference standards which ensure international comparability to assist clinicians in diagnosing cases of delayed or advanced tooth eruption. 7,8 While mean ages of eruption for primary dentition have been determined for most population groups [1][2][3][4][5][6] , a review of the literature revealed no reported data on Saudi Arabian children.…”
Section: Introductionmentioning
confidence: 99%